SOFTWARE REQUIREMENT SPECIFICATION SISTEM INFORMASI AKUNTANSI USAHA PETERNAKAN DAN PENJUALAN TELUR - Susilowati, Meme; Wibisono Hartanto, Christian Adri; Tirma Irawan , Paulus Lucky (Fakultas Sains dan Teknologi, 2023)
East Java is one of the largest egg producing provinces in Indonesia. This is because the number of chicken farms is increasingly developing in every region, especially in the province of East Java. One of the farms that is currently developing is CV Semeru in Blitar City. This company has one problem in the financial department which is still manual in recording & reporting finances using Excel. Therefore, an accounting information system is needed to overcome company problems so that financial recording and reporting becomes accurate & efficient. In system development, a system requirements analysis is required which produces a software requirements specification document. This research aims to create SRS documentation so that it can become a reference for developers in developing accounting information systems. All stages in this research were made using the ISO/IEC/IEEE 29148:2018 Systems and software engineering – Life cycle processes – Requirements engineering standard as a reference in preparing the SRS document. With these stages, 30 functional requirements tables, 37 database tables, 78 UI forms can be produced to build an accounting information system, and there are outputs in the form of financial reports such as cash in and out reports, general journals, trial balances, ledgers, trial balances after adjustments. , adjusting journals, profit and loss, changes in capital, and final balance sheet.